Microplastic concentrations in two Oregon bivalve species: Spatial, temporal, and species variability. Issue 1 (12th November 2019) - Baechler, Britta R.; Granek, Elise F.; Hunter, Matthew V.; Conn, Kathleen E.
Abstract: Microplastics are an ecological stressor with implications for ecosystem and human health when present in seafood. We quantified microplastic types, concentrations, anatomical burdens, geographic distribution, and temporal differences in Pacific oysters ( Crassostrea gigas ) and Pacific razor clams ( Siliqua patula ) from 15 Oregon coast, U.S.A. sites. Microplastics were present in organisms from all sites. On average, whole oysters and razor clams contained 10.95 ± 0.77 and 8.84 ± 0.45 microplastic pieces per individual, or 0.35 ± 0.04 pieces g −1 tissue and 0.16 ± 0.02 pieces g −1 tissue, respectively. Contamination was quantified but not subtracted. Over 99% of microplastics were fibers. Material type was determined using Fourier‐transform infrared spectroscopy. Spring samples contained more microplastics than summer samples in oysters but not razor clams. Our study is the first to document microplastics in Pacific razor clams and provides important coast‐wide data to compare microplastic burden across species, seasons, and sites.